Design of a seven-element anti-jamming GPS antenna array - Lim, Jenny Woon Lee. (2012)
This project is to design and build a seven element anti jamming antenna which can provide 2 null signals in the direction of the jammer signal. The project was to be completed through two phases where the first phase was based on software design and second phase was based on hardware testing.